Superior electrochemical performance of SnSe-PPy nanocomposites for supercapacitor application - Yashna Anthony; Veena Ragupathi (Zaštita Materijala)
Recently, Metal chalcogenides have received considerable interest in the field of energy storage devices. In this work, tin selenide-polypyrrole (SnSe-PPy) nanocomposite has been synthesized by hydrothermal method and its supercapacitive behavior is investigated. The synthesized SnSe-PPy nanocomposite is analyzed by X-ray diffraction (XRD), Fourier transforms infrared spectroscopy (FTIR), Scanning electron microscopy (SEM) and electrochemical characterization. XRD confirms the existence of orthorhombic SnSe, and the FTIR result reveals the presence of polypyrrole. The supercapacitive behavior of SnSe-PPy nanocomposite is studied by cyclic voltammetry and galvanostatic charge-discharge studies. SnSe-PPy nanocomposite delivers the specific capacitance of 223 F g-1 at 10 mV sec -1. The addition of polypyrrole increases the conductivity of the material and improves its supercapacitive behavior.